Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The role of business incubators in Saudi universities in supporting entrepreneurial thought  in light of the knowledge economy and the requirements for its activation according  to reference documentsDr. Noof Atallah Alanazi, Dr. Etaf Lahig Alanazi, Dr. Norah Obaid Alsalhani2. The extent of social studies teachers’ familiarity with the values of integrity from the point of view of educational supervisors in Kingdom of Saudi ArabiaMr. Bandar Abdullah Mutlaq Almutlaq, Mrs. Wafa Abdullah Ali Alshehri3. A proposed vision for developing the academic performance of Saudi universities in light of lean managementCo-Prof. Elham Naief Al-Rajhi4. The State of Electronic Data Wall Usage on E-learning platforms from the Perspectives  of Middle School Female TeachersMrs. Muslihah Rashed Alluhaybi, Mrs. Rana Atif Sobahi5. Future Thinking among twelfth grade students in Government schools in Sultanate of Oman  in Light of Some VariablesDr. Issa Khamis Ali Al-Kharusi6. Teachers' Perception and Attitude towards Gifted Students Focusing on Their Giftedness Characteristics in Primary Schools in Riyadh: Kingdom of Saudi ArabiaMrs. Azizh Abdullah Almatroodi
Keywords: Journal of Educational and Psychological Sciences